Comparative Analysis on Clinical Characteristics Among Patients with Acute Hepatitis A Virus (HAV) and Patients with Acute Hepatitis E Virus (HEV): A Single-Center Retrospective Study from Bulgaria - Baymakova M; Kunchev M; Mihaylova-Garnizova R; Zasheva A; Plochev K; Kundurzhiev T; Tsachev I (Infection and Drug Resistance, 2023)
Magdalena Baymakova,1 Metodi Kunchev,2 Raynichka Mihaylova-Garnizova,1 Anelia Zasheva,1 Kamen Plochev,1 Todor Kundurzhiev,3 Ilia Tsachev4 1Department of Infectious Diseases, Military Medical Academy, Sofia, Bulgaria; 2Department of Virology, Military Medical Academy, Sofia, Bulgaria; 3Department of Occupational Medicine, Faculty of Public Health, Medical University, Sofia, Bulgaria; 4Department of Microbiology, Infectious and Parasitic Diseases, Faculty of Veterinary Medicine, Trakia University, Stara Zagora, BulgariaCorrespondence: Magdalena Baymakova, Department of Infectious Diseases, Military Medical Academy, Sofia, Bulgaria, Tel +359-882-28-50-87, Email dr.baymakova@gmail.comIntroduction: The acute viral hepatitis was one of the most common conditions in daily clinical practice varying in different parts of the world. The aim of the present study was to perform a comparative analysis on clinical characteristics among patients with acute hepatitis A virus (HAV) infection and patients with acute hepatitis E virus (HEV) infection admitted to the Military Medical Academy (MMA), Sofia, Bulgaria.Methods: A retrospective study was performed at MMA, between 1 January 2016 and 31 December 2021. The etiological diagnosis was confirmed by enzyme-linked immunosorbent assay (ELISA) HAV/HEV IgM serology assays.Results: The current survey included 231 patients with mean age 45.11 ± 16.08 years (95% confidence interval: 43.04– 47.19). According to the case definition, inclusion and exclusion criteria, persons were divided into two groups: patients with acute HAV infection (68.4%; 158/231) and patients with acute HEV infection (31.6%; 73/231). Males with HEV had 3.091 times the odds of comorbidity “hypertension” than males with HAV (p = 0.032). There were almost equal odds of increased ALT (odds ratio = 0.999; p = 0.003) in men with HEV and men with HAV. Females with HEV had 5.161 times the odds of comorbidity “hypertension” compared with females with HAV (p = 0.049). We found almost equal odds for elevated ALT in women with HEV and women with HAV (OR = 0.999; p = 0.025). In the non-elderly group (< 60-year-old), HEV individuals had 4.544 and 10.560 times the odds of comorbidities “hypertension” and “cardiovascular diseases” compared with HAV patients (p < 0.05). We found almost equal odds for elevated ALT in HEV patients and HAV participants (OR = 0.998; p = 0.002).Conclusion: The results from the current study may support the physicians daily care for patients with acute HAV and acute HEV.Keywords: Bulgaria, clinical characteristics, hepatitis A virus, HAV, hepatitis E virus, HEV, single-center study